BIOREMEDIASI LIMBAH CAIR KELAPA SAWIT DENGAN MENGGUNAKAN Spirogyra sp - Baihaqi Baihaqi; Mujibul Rahman; Ilham Zulfahmi; Muslich Hidayat (Biotik, 2017)
One type of algae that potentially reduces palm oil mill effluent is Spirogyra sp. Spirogyra sp. Has a wide distribution on the coast of Indonesia and is still underutilized by pond farmers. This study aims to test the efficiency of Spirogyra as a bioremediation agent of palm oil liquid waste and to examine the effect of palm oil liquid waste on the growth of Spirogyra. This research was conducted from March to July 2017. The research design consisted of five treatments, treatment A control (0 mL.L-1), B treatment (25 mL.L-1), C treatment (50 mL.L-1) ), Treatment D (75 mL.L-1) and E treatment (100 mL.L-1). Observation parameters include absolute growth, relative growth rate, doubling time and water quality parameters (pH, temperature, salinity, dissolved oxygen and COD). The stastistic analysis used in this study uses one way ANOVA. The obvious different criteria used in this study was at a 95% confidence level (p